Unlocking happiness: how crafting your career path boosts life satisfaction through forward thinking and self-confidence in career choices - Hanan Eid Badwy; Sikandar Ali Qalati; Mohamed Fawzy El-Bardan (Humanities & Social Sciences Communications)
Abstract Career construction theory (CCT) asserts that a substantial degree of career adaptability (CA) correlates with favorable outcomes when individuals undergo different environments. Building upon the theoretical framework of the CCT, our study hypothesized that the nexus between CA and life satisfaction (LS) as an outcome of adaptation is mediated by future orientation (FO) and career decision-making self-efficacy (CDMSE). We gathered data from 317 graduates in Greater Cairo, Egypt. The data was collected through a self-administered questionnaire and analyzed using partial least square structural equation modeling (PLS-SEM) via WarpPls 7.0 software. Our findings indicate a positive correlation between CA and LS and a positive link between CA and FO and CDMSE. Additionally, FO and CDMSE were found to be positively related to LS. However, contrary to the expectations, FO was not identified as a mediating factor between CA and LS, while CDMSE did serve as a mediator between CA and LS. Based on these results, managers can provide workshops and training opportunities to enhance graduates’ confidence and assist them in developing plans, ultimately leading them to increased satisfaction in life.